2018
DOI: 10.1177/1077546318769558
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic simulation of the oscillation characteristics of supercritical carbon dioxide impacting jets

Abstract: A numerical model was established to investigate the dynamic oscillation characteristics of supercritical carbon dioxide (sc-CO2) impacting jets. The jet hydrodynamics, heat transfer, and physical properties of sc-CO2 fluid were incorporated into the model. The coupling of multiple fields with large velocity and pressure gradients was achieved using a modified SIMPLE segmentation algorithm. Laboratory experiments validated the reliability of the numerical model by detecting dynamic changes in the pressure on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The EOS for the CO 2 is even more critical than the turbulence model for compressible fluids [20]. In the trans-critical state, the state parameters of CO 2 vary drastically, especially in the shockwave.…”
Section: Real Gas Model For Comentioning
confidence: 96%
See 1 more Smart Citation
“…The EOS for the CO 2 is even more critical than the turbulence model for compressible fluids [20]. In the trans-critical state, the state parameters of CO 2 vary drastically, especially in the shockwave.…”
Section: Real Gas Model For Comentioning
confidence: 96%
“…Computational fluid dynamics (CFD) simulation has become a valuable method to study the flow field of the under-expanded CO 2 jet. For instance, Zhang et al [20] established a numerical model to investigate the dynamic oscillation characteristics of SC-CO 2 . Zhou et al [21] developed a numerical model to study the flow field characteristics of an SC-CO 2 impacting jet at the well bottom.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the oscillation of the shock wave and the feedback effect on the flow field, fluctuations in pressure are caused by the impinging surface of the target. The pressure fluctuation characteristics on the surface of the plate were also observed for under-expansion shocks, indicating the pressure fluctuations induced by a compressible jet flow. The flow field analysis of the impinging jets has been studied extensively, where their characterization has been used in many engineering applications . Yaga et al found that stagnation pressure on the plate depends on the pressure in the chamber and the distance between the nozzle to the plate.…”
Section: Introductionmentioning
confidence: 99%
“…For the simulation of the SC-CO 2 jet, both the equation of state (EOS) and the choice of simulation method are key parameters for the accuracy of the result. 29 For instance, Zhang et al 24 have established a numerical model to investigate the dynamic oscillation characteristics of SC-CO 2 by using a standard k– ε turbulence model. Wang et al 30 used the Peng–Robinson EOS to compute the thermodynamic properties and the structure of the under-expanded jet of CO 2 .…”
Section: Introductionmentioning
confidence: 99%